Factors Affecting Substrate Heating with Printed Thermites. Issue 12 (27th October 2021) - Ervin, Matthew H.
Abstract: Various nano‐aluminum thermites were printed and burned on substrates. The reactions were recorded using high‐speed and infra‐red videography in order to investigate the factors affecting the resulting substrate heating. A large number of factors are found to affect the achieved substrate temperature. The thermite's exothermic energy release, gas generation, and burn rate are significant factors, as are the substrate's mass and thermal conductivity. Full‐thickness heating to 360 °C is demonstrated for a standard glass microscope slide. This work will hopefully inspire new applications in actuators or on‐chip thermal processing utilizing the high energy density of printed thermites. Abstract :